2013
DOI: 10.1016/j.foodres.2011.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultra high temperature (UHT) treatment on coffee brew stability

Abstract: In this work, the influence of an Ultra High Temperature (UHT) treatment on chemical and sensory composition of Arabica coffee brews for a longer shelf-life has been studied. A temperature of 120 ºC for 2 s allows to obtain a microbiologically safe coffee brew, good valued from the sensory point of view. The behavior of the UHT vs non UHT treated coffee brew was followed throughout 120 days of storage at 4 ºC. The UHT treatment keeps longer the typical acidity of the brews, delaying and softening the pH decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
(37 reference statements)
2
15
3
1
Order By: Relevance
“…However, most of the L* values somewhat increased during storage. This result was not corresponded with Sopelana et al (2013) who reported that the L* value of coffee brews slightly decreased and is distributed between approximately 19.77 to 25.60 during storage at 4℃. The L* value of the milk beverages was higher than the results from Sopelana et al (2013).…”
Section: Changes In Color and Brownness Of Milk Beveragescontrasting
confidence: 94%
See 1 more Smart Citation
“…However, most of the L* values somewhat increased during storage. This result was not corresponded with Sopelana et al (2013) who reported that the L* value of coffee brews slightly decreased and is distributed between approximately 19.77 to 25.60 during storage at 4℃. The L* value of the milk beverages was higher than the results from Sopelana et al (2013).…”
Section: Changes In Color and Brownness Of Milk Beveragescontrasting
confidence: 94%
“…This result was not corresponded with Sopelana et al (2013) who reported that the L* value of coffee brews slightly decreased and is distributed between approximately 19.77 to 25.60 during storage at 4℃. The L* value of the milk beverages was higher than the results from Sopelana et al (2013). It is thought that the L* values of this study were higher than that of the researchers due to the addition of milk in the sample for this study.…”
Section: Changes In Color and Brownness Of Milk Beveragescontrasting
confidence: 94%
“…Furans, such as furfural, furfuryl alcohol, and furfuryl acetate, are responsible for toasted odour notes, such as burnt, caramellike, and smoke (Cheong et al, 2013;Roldán et al, 2003;Toci and Farah, 2008;Caporaso et al, 2014;Piccino et al 2014). Pirazines are a dominant group of volatile compounds in coffee aroma that are associated with roast and earth odour notes (Budryn et al, 2011;Cheong et al, 2013;Korhonová et al, 2009;Sopelana et al, 2013;Sunarharum et al, 2014).…”
Section: Volatile Compound Analysismentioning
confidence: 99%
“…It has been observed that the distribution of ice crystals of different sizes depends not only on the freezing rates but also on the sample size and freezing direction, among other variables (Hottot et al 2007). On the other hand, the sensory attributes of the coffee beverage is one of its most important quality parameters, consequently, sensory analysis is the most used technique to evaluate coffee quality (Cheong et al, 2013;MacLeod et al, 2006;Sopelana et al, 2013;Farah et al, 2006). However, there are few reported works on the efficacy of volatile compound preservation when using FC (Ramos et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Chlorogenic acid (3-caffeoylquinic acid), cryptochlorogenic acid (4-caffeoylquinic acid), neoclorogenic acid (5-caffeoylquinic acid) and caffeine are the major bioactive compounds present in coffee (Ferruzzi, 2010;Fujioka & Shibamoto, 2008;Sopelana et al, 2013;Vignoli et al, 2011). The block FC method has been shown to retain nutritional and functional properties of the product using low processing temperatures (Belén et al, 2013;Boaventura et al, 2012); however, this effect has not been tested for coffee extracts.…”
Section: Introductionmentioning
confidence: 99%